Green Open Access in Lithuania - Kepalienė, Fausta (Knygotyra, 2020)
Favorable conditions for the development of open access have been created in Lithuania: in the absence of scholarly commercial publishing, some scholarly journals in 1999 were already freely available on the Internet. eLABa, in 2011 launched as a national repository, laid the foundation for the development of “green” open access in Lithuania. Currently 13 repositories in Lithuania are maintained and various legal acts related to the implementation of open access in the country have been adopted. The aim of this article is to analyze how “green” open access is being developed in Lithuania in terms of infrastructure, regulation, and implementation. International, national, and institutional documents regulating the implementation of open access were analyzed using the document analysis method. The analysis showed that a legal environment which complies with the provisions of international documents regulating open access has been formed. In the analyzed documents, the authors of Lithuanian scholarly publications are required to submit their peer-reviewed publications to eLABa or another specified repository within a specific period. This requirement, as shown by the analysis of statistical indicators of the national repository eLABa, is fulfilled to a very small extent. Only 3.4% of all scholarly publications for which metadata had been submitted to eLABa were uploaded as full text documents at the end of 2019. It means that scholars provide bibliographic data on publications to eLABa, but upload only a small part of the full-text documents to it. One of the reasons for the low level of activity in promoting scholarly publications to eLABa could be that most Lithuanian scholarly journals are open access in nature and are already publicly available. Also, uploading a full-text scholarly publication to a repository, not just registering it, does not have a direct impact on the attestation of the researchers at most universities in Lithuania. However, the low use of institutional repositories as a channel for publishing scholarly publications is a common problem not only in Lithuania, but also in other countries. There is a global trend of subject repositories being used for the dissemination of full-text scholarly publications, while institutional repositories – for providing bibliographic information on research output and uploading student works. This situation, where only a very small proportion of all registered scholarly publications are uploaded to institutional repositories, does not allow scientific institutions to ensure the long-term preservation of scholarly works. In general, it can be seen that the debate on open access and, at the same time, the way to implement “green” open access, is becoming more and more concrete, focusing on specific, practical issues. Instead of considering whether open access is needed, discussion is moved on to the question of what measures should be taken to address the lower-than-expected scholars’ involvement in the implementation of open access publishing. Therefore, the research of scholars’ open access publishing behaviour is important in order to better understand the needs of authors for the dissemination of open access scholarly publications. In the case of the implementation of “green” open access in Lithuania, it is important to find out what determines the choice of the scholars to provide or not publications to eLABa and / or international repositories as well as to investigate if there is a need to create Lithuanian subject-based repositories.